PENGUKURAN ASPEK KEBUGARAN JASMANI KELENTUKAN MENGGUNAKAN INSTRUMEN V-SIT AND REACH TEST - Wicaksono, Arrijal (Universitas Negeri Surabaya, 2021)
Physical fitness is the ability to perform various activities or a job in daily life and adapt to physical loading without the effects of excessive fatigue. In carrying out various activities, a person needs to increase good flexibility in protecting the body from various kinds of injuries. One of them is flexibility where the physical components of each person have a form of movement that is not rigid, smooth, and flexible. Flexibility in students can be done using the v-sit and reach test instrument. The approach in this study uses a quantitative approach model where the researcher places more emphasis on data analysis numerically or numerically. The analysis will be processed data using statistical methods. This research is useful in knowing aspects of physical fitness and flexibility of junior high school students (SMP) Bangkalan 1 using the v-sit and reach test and to determine differences in student flexibility based on gender. From the results of the study, it was found that the flexibility of students at SMP Negeri 1 Bangkalan, Bangkalan Regency resulted in a good category with a total of 5 people or 16.6% and a very good category with a total of 3 people as much as 10%. Meanwhile for the sufficient category as many as 8 people or 26.6%, for the less type category there are 14 people as much as 46.6%. Meanwhile, the category with the least type has a number that is not left or as much as 0%.